Early Childhood Nutrition Education Mentoring for Parents and Teachers at PAUD Samratulangi in Manado City - Alpinia Pondagitan; Rakhmawati Agustina (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Balanced nutrition in early childhood is very important in achieving optimal growth and development, because in this period children begin to learn what, when and how to eat either through direct experience or seeing other people which will have an impact on their developmental health.  Increased in health problems on children mainly caused by various factors including parent economic status, parenting patterns, and the level of knowledge and awareness of healthy and nutritious food on children. This will potentially lead to new health problems and will have an impact on children’s growth and development which will affect their productivity in the future. The purpose of this community service is to carry out mentoring for early childhood nutrition education for parents and teachers at PAUD Samratulangi in Manado City. The targets are parents and teachers at PAUD Samratulangi in Manado City. The activity was held on June 11th, 2022 with several stages including preparation stage, implementation stage, and evaluation stage. The preparation stage is carried out by conducting survey location and obtaining permits at the activity site. Implementation is carried out by providing balanced nutrition assistance to parents and teachers. Evaluation is carried out by collecting data from the impelentation activities, in this case by providing a knowledge questionnaire about balanced nutrition for early childhood. The result of this activity is the impelentation of balanced nutrition assistance to parents and teachers. The implementers of this community service activities are lecturers and undergraduate students form the Nutrition Program, Faculty of Health Sciences, University of Muhammadiyah Manado